Rethinking HIV care for youth: Insights from qualitative research with youth in Chad - Esias Bedingar; Ferdinan Paningar; Ngarossorang Bedingar; Eric Mbaidoum; Naortangar Ngaradoum; Rifat Atun; Aisha K. Yousafzai (PLoS ONE, 2025)
Youth ages 15–24 years are significantly impacted by the HIV/AIDS epidemic, representing approximately 37% of new infections globally. This demographic is especially vulnerable in sub-Saharan Africa, where over 80% of HIV-positive youth reside. In Chad, youth face barriers to effective HIV care, including high prevalence rates, particularly among young women, and substantial disparities across regions. Despite overall reductions in new HIV infections, youth remain disproportionately affected, necessitating targeted interventions to improve HIV care outcomes. This study represents a secondary data analysis derived from a parent study that employed a grounded theory design to develop theory inductively. The secondary analysis aimed to generate an in-depth understanding of the pathways to care for youth in Chad, exploring barriers and facilitators across the care continuum, from diagnosis to antiretroviral therapy (ART) adherence. Data were collected through focus group discussions with 52 youth and 48 service providers, including healthcare workers and community actors. Data were transcribed, translated, and analyzed assisted with ATLAS.ti software (Version 7.6.3). Youth identified barriers such as financial constraints, logistical challenges, and fear of stigma, while facilitators included peer support and specialized HIV care facilities. Healthcare workers emphasized the critical role of psychosocial counseling and confidentiality in facilitating youth engagement with HIV services. They also highlighted critical challenges, including the lack of accessible and youth-friendly services, and the need for continuous education to reduce stigma. The findings underscore the importance of tailored, youth-friendly interventions that address these challenges, foster supportive environments, and integrate youth and provider perspectives. We recommend redesigning healthcare services to improve accessibility, reduce stigma, and provide continuous psychosocial support, ultimately enhancing the HIV care continuum for youth in Chad and similar contexts.